Oral tablet-type adsorbent

JP7631577B2Active Publication Date: 2025-02-18FUTAMURA CHEM CO LTD
View PDF 14 Cites 0 Cited by

Patent Information

Application Number
JP2024020185
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2024-02-14
Publication Date
2025-02-18
Estimated Expiration
2040-08-26

Smart Images

  • Figure 0007631577000001
    Figure 0007631577000001
  • Figure 0007631577000002
    Figure 0007631577000002
  • Figure 0007631577000003
    Figure 0007631577000003
Patent Text Reader

Abstract

To provide a tablet-type adsorbent for oral administration that can reduce a decline in the performance of adsorbing toxic substances in activated carbon to reduce the burden on a patient to take a drug, even when the activated carbon as an adsorbent is formed into an easy-to-dose tablet form by using an additive as a binding agent.SOLUTION: Provided is a tablet-type adsorbent for oral administration that comprises granular or spherical activated carbon as an adsorbent, and an additive as a binding agent. The additive comprises at least one of sodium carboxymethyl cellulose and hydroxyethyl cellulose, and is added in an amount of 1.0 wt.% or less based on 100 wt.% of the tablet-type adsorbent.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a tablet-type adsorbent for oral administration, and more particularly to a tablet-type adsorbent for oral administration that uses activated carbon as an adsorbent, which has excellent adsorption performance for toxic substances. [Background technology]

[0002] Patients with kidney or liver disease accumulate toxic substances in their blood, which results in encephalopathy such as uremia and impaired consciousness. The number of such patients tends to increase year by year. To treat these patients, hemodialysis-type artificial kidneys that remove toxic substances from the body are used. However, such artificial kidneys require specialized technicians for safety reasons, and the physical, mental, and economic burden placed on patients when blood is removed from the body is problematic, and are not necessarily satisfactory.

[0003] As an alternative to artificial organs, oral adsorbents have been developed that are taken orally, adsorb toxic substances in the body, and excrete them from the body (see Patent Document 1, Patent Document 2, etc.). Anti-nephrotic syndrome drugs have been reported that use petroleum hydrocarbons (pitch) and the like as raw materials, adjust the particle size to be relatively uniform, and carbonize and activate them (see Patent Document 3, for example). Oral adsorbents have also been reported that attempt to adjust the distribution of the pore volume and other aspects of the activated carbon while making the particle size of the activated carbon relatively uniform (see Patent Document 4). In this way, medicinal activated carbon improves the poor fluidity in the intestine by making the particle size relatively uniform, and at the same time, improves the adsorption performance of the activated carbon by adjusting the pores. For this reason, it is taken by many patients with mild chronic renal failure.

[0004] Medicinal activated carbon is required to adsorb uremia causative substances and their precursors quickly and efficiently. However, it is difficult to reduce the particle size of existing medicinal activated carbon while maintaining the spherical shape. In addition, the adjustment of pores in conventional medicinal activated carbon is not good, and the adsorption performance is not necessarily sufficient, so the daily dose must be increased. In particular, patients with chronic renal failure are restricted in the amount of water they can take, so swallowing a small amount of water is very painful for them.

[0005] And, a tablet-type composition for oral administration has been proposed in which medicinal activated carbon is made into a tablet form and is easy to take (for example, see Patent Document 5). Since medicinal activated carbon is taken in a large amount, the volume of the administered dose is large, and since activated carbon does not dissolve in water, if it is in the form of fine granules, it leaves an unpleasant feeling in the mouth, and is not easy to take. Furthermore, if it is made into a capsule form, dead volume is created, so the volume of the administered dose becomes even larger and it tends to be difficult to swallow.

[0006] Although the tablet-type composition for oral administration mentioned above aims to reduce the burden on patients, the binder tends to block the pores on the surface of the activated carbon, reducing the adsorption performance, and there is a risk that the dosage must be increased due to the reduced adsorption performance. As a result, the burden on patients may not change much, or may even increase. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] Patent No. 3835698 [Patent Document 2] JP 2008-303193 A [Patent Document 3] Japanese Patent Application Publication No. 6-135841 [Patent Document 4] JP 2002-308785 A [Patent Document 5] Patent No. 5701971 Summary of the Invention [Problem to be solved by the invention]

[0008] Therefore, the present invention has been proposed in consideration of the above-mentioned circumstances, and provides a tablet-type adsorbent for oral administration which can suppress the deterioration of the adsorption performance of activated carbon for toxic substances, even when activated carbon as an adsorbent is formed into an easy-to-take tablet form by using an additive as a binder, thereby reducing the burden on patients when taking the adsorbent. [Means for solving the problem]

[0009] That is, the first invention is a tablet-type adsorbent for oral administration, which contains granular or spherical activated carbon as an adsorbent and an additive as a binder, characterized in that the additive contains at least one of sodium carboxymethylcellulose and hydroxyethylcellulose, and is added in an amount of 1.0% by weight or less relative to 100% by weight of the tablet-type adsorbent.

[0010] A second invention relates to the tablet-type adsorbent for oral administration according to the first invention, wherein the average particle size of the activated carbon is 20 to 1000 μm.

[0011] A third invention relates to the tablet-type adsorbent for oral administration according to the first or second invention, wherein the tablet-type adsorbent has a hardness of 10 N or more.

[0012] The fourth invention is the first to third inventions, wherein the sum of the micropore volumes of the activated carbon defined by the following formula (i) (V mic ) to the sum of mesopore volumes (V met ) volume ratio (V m ) is 5.0 or less.

[0013]

number

[0014] A fifth invention relates to a tablet-type adsorbent for oral administration according to any one of the first to fourth inventions, wherein the activated carbon is a resin carbonized product of a phenol resin. Effect of the Invention

[0015] According to the first invention, the tablet-type adsorbent for oral administration comprises granular or spherical activated carbon as an adsorbent and an additive as a binder, and the additive comprises at least one of sodium carboxymethylcellulose or hydroxyethylcellulose, and is added in an amount of 1.0% by weight or less relative to 100% by weight of the tablet-type adsorbent. Therefore, even when the activated carbon as an adsorbent is formed into a tablet shape that is easy to take by the additive as a binder, the deterioration of the adsorption performance of the activated carbon for toxic substances can be suppressed, and the burden on the patient when taking the tablet can be reduced.

[0016] According to the tablet-type adsorbent for oral administration of the second invention, since in the first invention, the average particle size of the activated carbon is 20 to 1000 μm, the surface area of ​​the activated carbon adsorbent can be ensured.

[0017] According to the third invention, the tablet-type adsorbent for oral administration in the first or second invention has a hardness of 10 N or more, which makes it possible to suppress breakage and wear of the tablet during transportation and packaging and to maintain the dosage form.

[0018] According to the fourth aspect of the present invention, in any one of the first to third aspects of the present invention, the sum of the micropore volumes (V mic ) to the sum of mesopore volumes (V met ) volume ratio (V m ) is 5.0 or less, the decrease in the adsorption performance of the activated carbon for toxic substances can be further suppressed, and the burden on patients of taking the drug can be reduced.

[0019] According to the fifth aspect of the present invention, in the tablet-type adsorbent for oral administration of any of the first to fourth aspects of the present invention, the activated carbon is a resin carbonized product of a phenol resin, and therefore it is possible to obtain activated carbon that can suppress the decrease in the adsorption performance of toxic substances when formed into a tablet shape. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0020] The tablet-type adsorbent for oral administration of the present invention is formed into a tablet shape using activated carbon as an adsorbent and an additive as a binder. The hardness of the formed tablet-type adsorbent is preferably higher than about 10 N. If the hardness is lower than 10 N, the tablet is likely to be damaged or worn during transportation or packaging, and the dosage form may not be maintained.

[0021] In addition, the activated carbon is preferably a resin carbonized product of a phenolic resin. By using a phenolic resin as the raw material of the activated carbon, the ratio (volume ratio) of the sum of the mesopore volume to the sum of the micropore volume can be increased while increasing the activation and increasing the specific surface area, and the adsorption performance of toxic substances can be easily improved. Examples of the phenolic resin include known ones such as novolac type, resol type, and composite phenolic resins of both. The phenolic resin is preferably in a range that results in granular or spherical activated carbon with an average particle size of 20 to 1000 μm. If the average particle size of the activated carbon is smaller than 20 μm, the activated carbon may become too dense when made into a tablet, resulting in poor disintegration. If the average particle size of the activated carbon exceeds 1000 μm, the surface area where the activated carbon comes into contact with each other and bonds with each other due to the additive as a binder increases, so that the binding force is weakened and the hardness of the tablet may be reduced.

[0022] In addition to phenolic resin, cellulose can be used as a raw material for activated carbon. When cellulose is used, it is believed that by making activated carbon with many macropores, it is possible to suppress the decrease in adsorption performance derived from activated carbon when it is made into a tablet form using additives.

[0023] In the present invention, as shown in the examples described later, it is preferable that the activated carbon is derived from a phenol resin and has a packing density of 0.3 to 0.5 g / ml, and the sum of the micropore volumes (V mic ) to the sum of mesopore volumes (V met ) volume ratio (V m ) is 5.0 or less, it is possible to suppress a decrease in the adsorption performance derived from the activated carbon when the activated carbon is made into a tablet form using an additive.

[0024] The phenol resin is placed in a firing furnace such as a cylindrical retort electric furnace, and the inside of the furnace is kept under an inert atmosphere of nitrogen, argon, helium, etc., and carbonized at 300 to 1000°C, preferably 450 to 700°C, for 1 to 20 hours to become a resin carbonized product (the "carbonization process").

[0025] After the carbonization step, the resin carbonized material is placed in a known heating furnace or the like and activated with steam at 750 to 1000°C, preferably 800 to 1000°C, and further 850 to 950°C ("activation step"). The activation time is 0.5 to 50 hours, depending on the production scale, equipment, etc. Alternatively, gas activation such as carbon dioxide may also be used. The activation time is appropriately adjusted depending on the physical properties of the target activated carbon. The activated carbon after activation is washed with dilute hydrochloric acid. The activated carbon after washing with dilute hydrochloric acid is washed with water until the pH is 5 to 7, for example, as measured according to JIS K 1474 (2014).

[0026] After washing with dilute hydrochloric acid, the activated carbon adsorbent is heated in a mixed gas of oxygen and nitrogen and washed with water as necessary to remove impurities such as ash. Residual hydrochloric acid and the like are removed by the heat treatment. The amount of surface oxides on the activated carbon adsorbent is adjusted by undergoing each treatment. After acid washing, the amount of surface oxides on the activated carbon adsorbent is increased through the heat treatment of the activated resin carbonized material. The oxygen concentration during this treatment is 0.1 to 21% by volume. The heating temperature is 150 to 1000°C, preferably 400 to 800°C, and the heating time is 15 minutes to 2 hours.

[0027] After the activation treatment or after the heat treatment following the activation treatment, the resin carbonized material (activated carbon adsorbent) is preferably sorted by sieving into granular or spherical activated carbon with an average particle size of 20 to 1000 μm, more preferably 150 to 350 μm. By adjusting and separating the particle size, the adsorption speed of the activated carbon adsorbent can be made constant and the adsorption capacity can be stabilized. Although the range of the particle size is not particularly limited, the above range can ensure the surface area of ​​the activated carbon adsorbent. Furthermore, when the particle size is uniform, the adsorption performance in the digestive tract can be stabilized. Moreover, the hardness of the particles is maintained, and further powdering in the digestive tract after oral administration (after ingestion) is suppressed. Therefore, the shape of the activated carbon for the adsorbent for oral administration is preferably spherical. However, since variations in sphericity due to manufacturing are also acceptable, granular shapes are also included.

[0028] Since phenolic resin has an aromatic ring structure in the molecule, the carbonization yield is increased. Furthermore, activation produces activated carbon with a large surface area. The activated carbon after activation has a small pore size and a high packing density, even compared to conventional activated carbon made from wood, coconut shells, petroleum pitch, etc. Therefore, it is suitable for adsorption of ionic organic compounds with relatively small molecular weights (molecular weights ranging from tens to hundreds) containing nitrogen, such as indoxyl sulfate, aminoisobutyric acid, tryptophan, etc., which are representative of causative substances of uremia and their precursors. Furthermore, phenolic resin has less ash content, such as nitrogen, phosphorus, sodium, magnesium, etc., and a higher ratio of carbon per unit mass, compared to conventional activated carbon raw materials such as wood. Therefore, activated carbon with fewer impurities can be obtained.

[0029] The activated carbon is required to adsorb the causative substances of liver dysfunction and kidney dysfunction as quickly as possible, as described in the examples below, and to exhibit sufficient adsorption performance with a relatively small dose. In order to find a harmonious range of properties that it should possess, the activated carbon is specified by indicators such as mercury pore volume value and BET specific surface area. As is clear from the trends in the examples below, it has been found that, among the indicators, when the value of the BET specific surface area is a certain value or more and the volume ratio of the sum of the mesopore volume to the sum of the micropore volume is a certain value or less, the decrease in adsorption performance is suppressed when the activated carbon is made into a tablet form.

[0030] The packing density is specified as 0.3 to 0.5 g / ml. In the present invention, the additive as a binder for forming the activated carbon into a tablet-type adsorbent is a very small amount of 1.0 wt% or less with respect to 100 wt% of the tablet-type adsorbent. In order to obtain a tablet-type adsorbent with excellent selective adsorption with a small amount of additive, it is convenient to have a low packing density of the activated carbon. However, if the packing density is less than 0.3 g / ml, the dosage increases and it becomes difficult to swallow when administered orally. If the packing density is more than 0.5 g / ml, the desired balance of selective adsorption may be lost, or the adsorption performance of the activated carbon may be significantly reduced by the additive.

[0031] The volume ratio of the sum of the mesopore volume to the sum of the micropore volume (V m ) is regulated to 5.0 or less as mentioned above. When the volume ratio is less than 5.0, it can be said that the activated carbon has mesopores developed to a certain degree. When mesopores are developed, even if the additive, which is a relatively large molecule, blocks some of the mesopores when the activated carbon is made into a tablet form using the additive, it is possible to introduce toxic substances into the micropores through other mesopores, and it is therefore considered that a decrease in the adsorption performance of toxic substances can be suppressed. The packing density is 0.3 to 0.5 g / ml, and the volume ratio (V m ) is 5.0 or less, the decrease in the adsorption performance of toxic substances is further suppressed. Furthermore, the BET specific surface area is 1200 m 2 / g or more is recommended. 2 When the adsorbent has a molecular weight of 1000 or more, the adsorbent has high adsorption performance for toxic substances and is therefore suitable as an adsorbent for oral administration.

[0032] As mentioned above, activated carbon is also determined by the pore size. In the case of an adsorbent such as activated carbon, there are micropores, mesopores, and macropores. The adsorption target and performance of activated carbon change depending on which range of pores is developed more. The activated carbon desired in the present invention is assumed to adsorb low molecular weight ionic organic compounds containing nitrogen, such as indoxyl sulfate, aminoisobutyric acid, tryptophan, which are representative of causative substances of uremia and their precursors. The activated carbon of the tablet-type adsorbent for oral administration of the present invention adsorbs the molecules to be adsorbed more effectively than conventional activated carbon adsorbents.

[0033] By increasing the ratio of macropores and mesopores relatively, the adsorption target can easily penetrate into the inside of the activated carbon. Even if an additive, which is a relatively large molecule, is adsorbed into the mesopores, the toxic substance is not easily hindered from reaching the micropores. The adsorption target is captured by the micropores connected to the macropores and mesopores, and adsorption proceeds quickly. Normally, the time from ingestion to excretion during which food is broken down by digestion and flows through the small intestine is thought to be about 6 to 10 hours. In other words, while flowing through the small intestine, the tablet-type adsorbent for oral administration (activated carbon) needs to adsorb the small molecules containing nitrogen, which are the target of adsorption. Therefore, considering efficient adsorption in the intestinal tract, it can be said that short-term adsorption is desirable. For these reasons, it is meaningful to develop many pores on the macropore side of the activated carbon.

[0034] In addition to these indicators, the average pore diameter can also be mentioned. Therefore, it is preferable that the average pore diameter is in the range of 1.5 to 2.5 nm. By adjusting the average pore diameter of the activated carbon adsorbent within this range, the adsorption of relatively low molecular ionic organic compounds with molecular weights of several tens to several hundreds becomes even better. At the same time, the activated carbon can suppress the adsorption of polymeric compounds necessary for living organisms, such as enzymes and polysaccharides, with molecular weights of several thousand to several tens of thousands. If the average pore diameter of the activated carbon exceeds 2.5 nm, it is not preferable because there are many pores that adsorb polymers such as enzymes and polysaccharides. In addition, if the average pore diameter of the activated carbon is less than 1.5 nm, the pore volume itself decreases, which may reduce the adsorption power.

[0035] The above-mentioned activated carbon is used as a drug for oral administration, and is a therapeutic or preventive agent for kidney disease or liver disease. The causative substances of disease and chronic symptoms are adsorbed and retained in the pores developed on the surface of the activated carbon, and are excreted from the body, suppressing the deterioration of symptoms and leading to improvement of the pathological condition. Furthermore, in cases where there is a congenital or acquired metabolic disorder or a risk of such an abnormality, the concentration of the causative substances of disease and chronic symptoms in the body can be reduced by taking activated carbon in advance. Therefore, it can also be taken as a preventative measure to prevent the worsening of symptoms.

[0036] Examples of renal diseases include chronic renal failure, acute renal failure, chronic pyelonephritis, acute pyelonephritis, chronic nephritis, acute nephritic syndrome, acute progressive nephritic syndrome, chronic nephritic syndrome, nephrotic syndrome, nephrosclerosis, interstitial nephritis, tubulopathy, lipoid nephrosis, diabetic nephropathy, renal vascular hypertension, hypertensive syndrome, or secondary renal disease associated with the above primary disease, and further, mild renal failure before dialysis. Examples of liver diseases include fulminant hepatitis, chronic hepatitis, viral hepatitis, alcoholic hepatitis, hepatic fibrosis, liver cirrhosis, liver cancer, autoimmune hepatitis, drug-induced allergic liver disorder, primary biliary cirrhosis, tremor, encephalopathy, metabolic disorder, and functional disorder.

[0037] The dosage of activated charcoal when used as an adsorbent for oral administration is difficult to specify because it is affected by factors such as age, sex, physique, and medical condition. However, in general, for humans, it is expected that the amount of activated charcoal to be administered is 1 to 20 g per day, 2 to 4 times a day. In terms of volume, this is 2 to 6 cm 3 It is necessary to take the medicine all at once, which is very painful for patients. Therefore, by making it into a tablet form, we hope to make it easier to take and reduce the burden on patients.

[0038] Because activated carbon cannot be tableted by conventional methods due to its nature, it is formed into a tablet shape by the binding force of a binder via a solvent such as water. When it is formed into a tablet shape using an additive as a binder, the additive covers the pores on the surface of the activated carbon, which tends to block the pores and reduce the adsorption performance of the activated carbon. If the adsorption performance of the activated carbon decreases due to the formation into a tablet shape, the dosage may increase, which increases the burden on the patient. In other words, it is necessary to suppress the decrease in the adsorption performance of the activated carbon when forming into a tablet shape.

[0039] Therefore, as mentioned above, the amount of additive added as a binder is set to 1.0 wt %, and the activated carbon is formed into a tablet shape using a very small amount of additive. In order to make it possible to form the activated carbon into a tablet shape using a small amount of additive, the packing density of the activated carbon is set to 0.3 to 0.5 g / ml, which makes it possible to form the activated carbon into a tablet shape and suppresses the deterioration of the adsorption performance of the activated carbon. Furthermore, the volume ratio of the sum of the mesopore volume to the sum of the micropore volume of the activated carbon (V m ) to a certain level or less, the degradation of the adsorption performance of the activated carbon when molded into a tablet form is suppressed.

[0040] The additive as a binder is at least one of sodium carboxymethylcellulose or hydroxyethylcellulose, and these additives allow the activated carbon to be formed into a tablet shape even with a small amount of additive, so that the increase in the dosage or dosage volume can be suppressed compared to fine granule-type adsorbents. The additive may be one of the above, or both may be mixed, or other additives may be mixed. In addition, a disintegrant may be used in combination to compensate for the disintegration of the tablet. EXAMPLES

[0041] [Preparation of activated carbon] The following activated carbons 1 to 5 were used in producing the tablet-type adsorbents for oral administration as prototypes. The phenol resin-derived activated carbons 1 to 5 corresponding to the prototypes were prepared by carbonizing and activating the raw phenol resin.

[0042] <Activated carbon 1> In a 1L separable flask, 160.0 parts by weight of 90% phenol, 111.8 parts by weight of 37% formaldehyde, 0.7 parts by weight of oxalic acid as an acid catalyst, 2.5 parts by weight of gum arabic as an emulsifier, and 168.8 parts by weight of water were added and heated to 95°C or higher to polymerize appropriately. Next, 147.0 parts by weight of 90% phenol, 143.1 parts by weight of formaldehyde, 19.3 parts by weight of hexamethylenetetramine and 8.3 parts by weight of triethylenetetramine as basic catalysts, and 41.4 parts by weight of water were added to the same separable flask, and the reaction was carried out by heating for 1 hour while maintaining at 60°C. Thereafter, the reaction was carried out by heating to 95°C or higher and refluxing for 4 hours to obtain a phenolic resin. 100g of the phenolic resin was placed in a cylindrical retort electric furnace, nitrogen was sealed in, and the temperature was raised at 100°C / hour until it reached 900°C. Thereafter, steam was injected into the furnace and the temperature was maintained at 900° C. for 2 hours for activation, and activated carbon 1 was obtained.

[0043] <Activated carbon 2> In a 1L separable flask, 98.0 parts by weight of 90% phenol, 53.2 parts by weight of 37% formaldehyde, 0.4 parts by weight of oxalic acid as an acid catalyst, 1.6 parts by weight of gum arabic as an emulsifier, and 147.9 parts by weight of water were added and heated to 95°C or higher to polymerize appropriately. Next, 189.0 parts by weight of 90% phenol, 220.3 parts by weight of 37% formaldehyde, 18.1 parts by weight of hexamethylenetetramine and 7.7 parts by weight of triethylenetetramine as basic catalysts, and 38.7 parts by weight of water were added to the same separable flask, and the reaction was carried out by heating for 1 hour while maintaining the temperature at 60°C. Thereafter, the mixture was heated to 95°C or higher and refluxed for 4 hours to obtain a phenolic resin. Activated carbon 2 was obtained in the same manner as activated carbon 1 except that the phenolic resin was used.

[0044] <Activated carbon 3> In a 1L separable flask, 163.0 parts by weight of 90% phenol, 88.6 parts by weight of 37% formaldehyde, 0.7 parts by weight of oxalic acid as an acid catalyst, 2.2 parts by weight of gum arabic as an emulsifier, and 152.6 parts by weight of water were added and heated to 95°C or higher to polymerize appropriately. Next, 126.6 parts by weight of 90% phenol, 177.1 parts by weight of 37% formaldehyde, 18.2 parts by weight of hexamethylenetetramine and 7.8 parts by weight of triethylenetetramine as basic catalysts, and 44.0 parts by weight of water were added to the same separable flask, and the reaction was carried out by heating for 1 hour while maintaining the temperature at 60°C. Thereafter, the mixture was heated to 95°C or higher and refluxed for 4 hours to obtain a phenolic resin. Activated carbon 3 was obtained in the same manner as activated carbon 1 except that the phenolic resin was used.

[0045] <Activated carbon 4> 500 g of phenolic resin (Lignite Corporation, "LPS-1046") was put into a cylindrical retort electric furnace and nitrogen was sealed in, then the temperature was raised at 100°C / 1 hour, and the temperature was maintained at 600°C for 1 hour to carbonize the phenolic resin in the furnace. The carbonized product was then heated to 900°C, steam was injected into the furnace, and the furnace was maintained at 900°C for 5 hours to activate the product, and activated carbon A was obtained. Furthermore, 80 g of the activated carbon A was put into a cylindrical retort electric furnace and nitrogen was sealed in, then the temperature was raised at 100°C / 1 hour, and the product was heated to 900°C. Steam was then injected into the furnace and the furnace was maintained at 900°C for 0.5 hours to further activate the product, and activated carbon 4 was obtained.

[0046] <Activated carbon 5> Activated carbon A produced in the preparation process of activated carbon 4 was used, and 80 g of the activated carbon A was placed in a cylindrical retort electric furnace and nitrogen was sealed in, after which the temperature was raised at 100° C. / hour and heated to 900° C. Thereafter, water vapor was injected into the furnace and maintained at 900° C. for 1 hour for further activation, and activated carbon 5 was obtained.

[0047] [Measurement of activated carbon] [BET specific surface area] Specific surface area (m 2 / g) was determined by measuring the nitrogen adsorption isotherm at 77 K using an automatic specific surface area / pore distribution analyzer (Microtrack-Bel Corporation, "BELSORP-miniII") and using the BET method (BET specific surface area).

[0048] [Filling density] Packing density (g / ml) was measured in accordance with JIS K 1474 (2014).

[0049] [Average particle size] The average particle size (μm) was measured using a laser light scattering particle size distribution analyzer (Shimadzu Corporation, "SALD3000S") and was taken as the particle size at an integrated value of 50% in the particle size distribution determined by the laser diffraction / scattering method.

[0050] [Micropore volume] In this specification, micropores are defined as pores having a pore diameter of less than 3 nm, and the sum of the micropore volumes (V mic ) (ml / g) was calculated as the sum of the pore volume of pores with diameters of less than 3 nm and the micropore volume (ml / g). Nitrogen adsorption isotherms were measured at 77K using an automatic specific surface area / pore distribution measuring device (Microtrack-Bel, "BELSORP-miniII"). From the obtained adsorption isotherms, calculations were performed for the range of pore diameters of less than 3 nm using the Saito-Foley trichromatic method using the attached analysis software. The various parameters used in the calculations are as follows: Diameter of the adsorbate molecule: 0.3000 nm Adsorbent atom diameter: 0.3400 nm Number of molecules of adsorbate per unit surface area in the adsorbed state: 8.5200E+18 molecules / m 2 Number of atoms per unit surface area of ​​adsorbent: 1.3100E+19 molecules / m 2 Magnetic susceptibility of the adsorbate molecule: 3.2500E-29cm 3 Magnetic susceptibility of adsorbent molecules: 1.3000E-29cm 3 Polarizability of the adsorbate molecule: 1.6300E-24cm 3 Polarizability of the adsorbent molecule: 2.5000E-24cm 3

[0051] [Mesopore volume] In this specification, mesopores are defined as pores having a pore diameter of 3 to 50 nm, and the sum of the mesopore volumes (V met ) (ml / g) was calculated using an Autopore 9500 (Shimadzu Corporation) with a contact angle of 130° and a surface tension of 484 dyne / cm (4.84 mN / m), and the pore volume value of pores with diameters of 3 to 50 nm measured by mercury intrusion porosimetry was calculated as the sum of the mesopore volumes (ml / g).

[0052] [Volume ratio] Volume ratio (V m ) is the sum of the micropore volumes (V mic ) (ml / g) is the sum of the mesopore volumes (V met ) (ml / g) and calculated using formula (i) above.

[0053] [Macropore volume] In this specification, macropores are defined as pores having a pore diameter of 50 to 15,000 nm, and the sum of the macropore volumes (ml / g) was determined using an Autopore 9500 (manufactured by Shimadzu Corporation) with a contact angle of 130° and a surface tension of 484 dyne / cm (4.84 mN / m) and the pore volume value of pores with diameters of 50 to 15,000 nm measured by mercury intrusion porosimetry.

[0054] The physical properties of activated carbons 1 to 5 are shown in Table 1. The BET specific surface area (m 2 / g), packing density (g / ml), average particle diameter (μm), sum of micropore volume (V mic ) (ml / g), the sum of mesopore volumes (V met )(ml / g), volume ratio (V m ) and the sum of the macropore volume (ml / g).

[0055] [Table 1]

[0056] [Additives used] The inventors used the following additives to obtain each prototype tablet-type adsorbent for oral administration. Sodium carboxymethylcellulose (CMC-Na): (manufactured by Daicel Corporation) Hydroxyethyl cellulose (HEC): (Sumitomo Seika Chemicals Co., Ltd.) Pullulan (PUL): (Hayashibara Co., Ltd.) Hydroxypropyl cellulose (HPC): (manufactured by Nippon Soda Co., Ltd.)

[0057] <Prototype example 1> 0.3018 g of activated carbon 1 was mixed with 0.0019 g of the additive sodium carboxymethylcellulose (CMC-Na) (0.6%) and 0.3177 g of water to form a kneaded mixture, which was then filled into a metal mold (molding die) with a diameter of 13 mm and a depth of 6 mm and molded. The mold was left to stand in a dryer, and then heated and dried at an internal temperature of 100°C for 1 hour or more. The mixture was then removed from the mold to form a tablet-type adsorbent for oral administration (Prototype Example 1).

[0058] <Prototype Example 2> A tablet-type adsorbent for oral administration (Prototype 2) was prepared in the same manner as the tablet-type adsorbent for oral administration (Prototype 1), except that the amount of activated carbon 1 was 0.3003 g, carboxymethylcellulose sodium (CMC-Na) (0.9%) was 0.0028 g, and water was 0.3827 g.

[0059] <Prototype 3> The oral tablet of Prototype 3 was prepared in the same manner as the oral tablet-type adsorbent of Prototype 1, except that the amount of activated carbon 1 was 0.2987 g, carboxymethylcellulose sodium (CMC-Na) (1.5%) was 0.0045 g, and water was 0.3532 g.

[0060] <Prototype 4> The oral tablet of Prototype Example 4 was prepared in the same manner as the oral tablet-type adsorbent of Prototype Example 1, except that the amount of activated carbon 1 was 0.2976 g, the amount of carboxymethylcellulose sodium (CMC-Na) (2.0%) was 0.0060 g, and the amount of water was 0.3694 g.

[0061] <Prototype 5> The oral tablet of Prototype Example 5 was prepared in the same manner as the oral tablet-type adsorbent of Prototype Example 1, except that the amount of activated carbon 2 was 0.3436 g, carboxymethylcellulose sodium (CMC-Na) (0.6%) was 0.0021 g, and water was 0.3293 g.

[0062] <Prototype 6> The tablet for oral administration of Prototype Example 6 was prepared in the same manner as the tablet-type adsorbent for oral administration of Prototype Example 1, except that the amount of activated carbon 2 was 0.3446 g, the amount of carboxymethylcellulose sodium (CMC-Na) (0.9%) was 0.0032 g, and the amount of water was 0.3617 g.

[0063] <Prototype 7> Except for using 0.3408 g of activated carbon 2, 0.051 g of sodium carboxymethylcellulose (CMC-Na) (1.5%), and 0.3438 g of water, the tablet-type adsorbent for oral administration was the same as that of Prototype Example 1, and an oral tablet was prepared as Prototype Example 7.

[0064] <Prototype Example 8> Except for using 0.3405 g of activated carbon 2, 0.0069 g of carboxymethylcellulose sodium (CMC-Na) (2.0%), and 0.3310 g of water, the same procedure was followed as for the tablet-type adsorbent for oral administration in Prototype Example 1, to give Prototype Example 8, a tablet for oral administration.

[0065] <Prototype Example 9> The oral tablet of Prototype Example 9 was prepared in the same manner as the oral tablet-type adsorbent of Prototype Example 1, except that the amount of activated carbon 3 was 0.3759 g, the amount of carboxymethylcellulose sodium (CMC-Na) (0.6%) was 0.0023 g, and the amount of water was 0.3317 g.

[0066] <Prototype Example 10> Except for using 0.3566 g of activated carbon 3, 0.0034 g of sodium carboxymethylcellulose (CMC-Na) (0.9%), and 0.3566 g of water, the same procedure was followed as for the tablet-type adsorbent for oral administration in Prototype Example 1, to give Prototype Example 10, a tablet for oral administration.

[0067] <Prototype Example 11> Except for using 0.3713 g of activated carbon 3, 0.0057 g of sodium carboxymethylcellulose (CMC-Na) (1.5%), and 0.3432 g of water, the same procedure was followed as for the tablet-type adsorbent for oral administration in Prototype Example 1, to give Prototype Example 11, a tablet for oral administration.

[0068] <Prototype Example 12> Except for using 0.3712 g of activated carbon 3, 0.0076 g of sodium carboxymethylcellulose (CMC-Na) (2.0%), and 0.3941 g of water, the same procedure was followed as for the tablet-type adsorbent for oral administration in Prototype Example 1, to give Prototype Example 12, a tablet for oral administration.

[0069] <Prototype Example 13> Except for using 0.5686 g of activated carbon 4, 0.0034 g of sodium carboxymethylcellulose (CMC-Na) (0.6%), and 0.3953 g of water, the same procedure was followed as for the tablet-type adsorbent for oral administration in Prototype Example 1, to give Prototype Example 13, a tablet for oral administration.

[0070] <Prototype Example 14> Except for using 0.5717 g of activated carbon 4, 0.0052 g of sodium carboxymethylcellulose (CMC-Na) (0.9%), and 0.3518 g of water, the same procedure was followed as for the tablet-type adsorbent for oral administration in Prototype Example 1, to give Prototype Example 14, a tablet for oral administration.

[0071] <Prototype Example 15> Except for using 0.5629 g of activated carbon 4, 0.0086 g of sodium carboxymethylcellulose (CMC-Na) (1.5%), and 0.4135 g of water, the same procedure was followed as for the tablet-type adsorbent for oral administration in Prototype Example 1, to give Prototype Example 15, a tablet for oral administration.

[0072] <Prototype Example 16> Except for using 0.5600 g of activated carbon 4, 0.0115 g of sodium carboxymethylcellulose (CMC-Na) (2.0%), and 0.4316 g of water, the same procedure was followed as for the tablet-type adsorbent for oral administration in Prototype Example 1, to give Prototype Example 16, a tablet for oral administration.

[0073] <Prototype Example 17> Except for using 0.5213 g of activated carbon 5, 0.0031 g of sodium carboxymethylcellulose (CMC-Na) (0.6%), and 0.3546 g of water, the same procedure was followed as for the tablet-type adsorbent for oral administration in Prototype Example 1, to give Prototype Example 17, a tablet for oral administration.

[0074] <Prototype Example 18> Except for using 0.5255 g of activated carbon 5, 0.0047 g of sodium carboxymethylcellulose (CMC-Na) (0.9%), and 0.4021 g of water, the same procedure was followed as for the tablet-type adsorbent for oral administration in Prototype Example 1, to give Prototype Example 18, a tablet for oral administration.

[0075] <Prototype Example 19> Except for using 0.5156 g of activated carbon 5, 0.0079 g of sodium carboxymethylcellulose (CMC-Na) (1.5%), and 0.4666 g of water, the same procedure was followed as for the tablet-type adsorbent for oral administration in Prototype Example 1, to give Prototype Example 19, a tablet for oral administration.

[0076] <Prototype Example 20> Except for using 0.5132 g of activated carbon 5, 0.0105 g of carboxymethylcellulose sodium (CMC-Na) (2.0%), and 0.4269 g of water, the same procedure was followed as for the tablet-type adsorbent for oral administration in Prototype Example 1, to give Prototype Example 20, a tablet for oral administration.

[0077] <Prototype Example 21> A tablet-type adsorbent for oral administration was prepared in the same manner as in Prototype Example 1, except that the amount of activated carbon 1 was 0.3019 g, hydroxyethyl cellulose (HEC) (0.6%) was 0.0018 g, and water was 0.2708 g, to give Prototype Example 21, a tablet-type adsorbent for oral administration.

[0078] <Prototype Example 22> A tablet-type adsorbent for oral administration was prepared in the same manner as in Prototype Example 1, except that the amount of activated carbon 1 was 0.3009 g, hydroxyethyl cellulose (HEC) (0.9%) was 0.0027 g, and water was 0.2862 g. This was used as Prototype Example 22, a tablet-type adsorbent for oral administration.

[0079] <Prototype Example 23> The oral tablet of Prototype 23 was prepared in the same manner as the oral tablet-type adsorbent of Prototype 1, except that the amount of activated carbon 1 was 0.2982 g, the amount of hydroxyethyl cellulose (HEC) (1.5%) was 0.0045 g, and the amount of water was 0.2777 g.

[0080] <Prototype Example 24> The oral tablet of Prototype 24 was prepared in the same manner as the oral tablet-type adsorbent of Prototype 1, except that the amount of activated carbon 1 was 0.2970 g, the amount of hydroxyethyl cellulose (HEC) (2.0%) was 0.0060 g, and the amount of water was 0.3180 g.

[0081] <Prototype Example 25> Except for using 0.3438 g of activated carbon 2, 0.0021 g of hydroxyethyl cellulose (HEC) (0.6%), and 0.3295 g of water, the same procedure was followed as for the tablet-type adsorbent for oral administration in Prototype Example 1, to give Prototype Example 25, a tablet for oral administration.

[0082] <Prototype Example 26> The oral tablet of Prototype 26 was prepared in the same manner as the oral tablet-type adsorbent of Prototype 1, except that the amount of activated carbon 2 was 0.3425 g, the amount of hydroxyethyl cellulose (HEC) (0.9%) was 0.0032 g, and the amount of water was 0.2979 g.

[0083] <Prototype Example 27> The oral tablet of Prototype 27 was prepared in the same manner as the oral tablet-type adsorbent of Prototype 1, except that the amount of activated carbon 2 was 0.3415 g, the amount of hydroxyethyl cellulose (HEC) (1.5%) was 0.0052 g, and the amount of water was 0.2941 g.

[0084] <Prototype Example 28> The oral tablet of Prototype 28 was prepared in the same manner as the oral tablet-type adsorbent of Prototype 1, except that the amount of activated carbon 2 was 0.3398 g, the amount of hydroxyethyl cellulose (HEC) (2.0%) was 0.0070 g, and the amount of water was 0.3163 g.

[0085] <Prototype Example 29> Except for using 0.3763 ​​g of activated carbon 3, 0.0024 g of hydroxyethyl cellulose (HEC) (0.6%), and 0.2992 g of water, the same procedure was followed as for the tablet-type adsorbent for oral administration in Prototype Example 1, to give Prototype Example 29, a tablet for oral administration.

[0086] <Prototype Example 30> Except for using 0.3739 g of activated carbon 3, 0.0034 g of hydroxyethyl cellulose (HEC) (0.9%), and 0.2702 g of water, the same procedure was followed as for the tablet-type adsorbent for oral administration in Prototype Example 1, to give Prototype Example 30, a tablet for oral administration.

[0087] <Prototype Example 31> The oral tablet of Prototype 31 was prepared in the same manner as the oral tablet-type adsorbent of Prototype 1, except that the amount of activated carbon 3 was 0.3703 g, the amount of hydroxyethyl cellulose (HEC) (1.5%) was 0.0058 g, and the amount of water was 0.3268 g.

[0088] <Prototype Example 32> The oral tablet of Prototype 32 was prepared in the same manner as the oral tablet-type adsorbent of Prototype 1, except that the amount of activated carbon 3 was 0.3698 g, the amount of hydroxyethyl cellulose (HEC) (2.0%) was 0.0076 g, and the amount of water was 0.3202 g.

[0089] <Prototype Example 33> The same procedure was followed as in Prototype 1 for the tablet-type adsorbent for oral administration, except that the amount of activated carbon 4 was 0.5683 g, the amount of hydroxyethyl cellulose (HEC) (0.6%) was 0.0034 g, and the amount of water was 0.03090 g, to give Prototype 33, a tablet for oral administration.

[0090] <Prototype Example 34> Except for using 0.5718 g of activated carbon 4, 0.0052 g of hydroxyethyl cellulose (HEC) (0.9%), and 0.3218 g of water, the same procedure was followed as for the tablet-type adsorbent for oral administration in Prototype Example 1, to give Prototype Example 34, a tablet for oral administration.

[0091] <Prototype Example 35> The oral tablet of Prototype 35 was prepared in the same manner as the oral tablet-type adsorbent of Prototype 1, except that the amount of activated carbon 4 was 0.5629 g, the amount of hydroxyethyl cellulose (HEC) (1.5%) was 0.0087 g, and the amount of water was 0.3733 g.

[0092] <Prototype Example 36> The oral tablet of Prototype 36 was prepared in the same manner as the oral tablet-type adsorbent of Prototype 1, except that the amount of activated carbon 4 was 0.5615 g, the amount of hydroxyethyl cellulose (HEC) (2.0%) was 0.0115 g, and the amount of water was 0.4142 g.

[0093] <Prototype Example 37> Except for using 0.5212 g of activated carbon 5, 0.0032 g of hydroxyethyl cellulose (HEC) (0.6%), and 0.4607 g of water, the same procedure was followed as for the tablet-type adsorbent for oral administration in Prototype Example 1, to give Prototype Example 37, a tablet for oral administration.

[0094] <Prototype Example 38> The oral tablet of Prototype 38 was prepared in the same manner as the oral tablet-type adsorbent of Prototype 1, except that the amount of activated carbon 5 was 0.5267 g, the amount of hydroxyethyl cellulose (HEC) (0.9%) was 0.0048 g, and the amount of water was 0.3348 g.

[0095] <Prototype Example 39> Except for using 0.5154 g of activated carbon 5, 0.0078 g of hydroxyethyl cellulose (HEC) (1.5%), and 0.4147 g of water, the same procedure was followed as for the tablet-type adsorbent for oral administration in Prototype Example 1, to give Prototype Example 39, a tablet for oral administration.

[0096] <Prototype Example 40> Except for using 0.5128 g of activated carbon 5, 0.0105 g of hydroxyethyl cellulose (HEC) (2.0%), and 0.4258 g of water, the same procedure was followed as for the tablet-type adsorbent for oral administration in Prototype Example 1, to give Prototype Example 40, a tablet for oral administration.

[0097] <Prototype Example 41> A tablet-type adsorbent for oral administration was prepared in the same manner as in Prototype 1, except that the amount of activated carbon 1 was 0.3002 g, the amount of pullulan (PUL) (0.6%) was 0.0019 g, and the amount of water was 0.3341 g. This was used as Prototype 41, a tablet-type adsorbent for oral administration.

[0098] <Prototype Example 42> A tablet-type adsorbent for oral administration was prepared in the same manner as in Prototype 1, except that the amount of activated carbon 1 was 0.2999 g, the amount of pullulan (PUL) (0.9%) was 0.0027 g, and the amount of water was 0.3251 g. This was used as Prototype 42, a tablet-type adsorbent for oral administration.

[0099] <Prototype Example 43> A tablet-type adsorbent for oral administration was prepared in the same manner as in Prototype 1, except that the amount of activated carbon 2 was 0.3441 g, the amount of pullulan (PUL) (0.6%) was 0.0021 g, and the amount of water was 0.3694 g. This was used as Prototype 43, a tablet-type adsorbent for oral administration.

[0100] <Prototype Example 44> Except for using 0.3420 g of activated carbon 2, 0.0032 g of pullulan (PUL) (0.9%), and 0.3657 g of water, the same procedure was followed as for the tablet-type adsorbent for oral administration in Prototype Example 1, to give tablet-type adsorbent for oral administration Prototype Example 44.

[0101] <Prototype Example 45> A tablet-type adsorbent for oral administration was prepared in the same manner as in Prototype 1, except that the amount of activated carbon 3 was 0.3764 g, the amount of pullulan (PUL) (0.6%) was 0.0024 g, and the amount of water was 0.3500 g. This was used as Prototype 45, a tablet-type adsorbent for oral administration.

[0102] <Prototype Example 46> A tablet-type adsorbent for oral administration was prepared in the same manner as in Prototype 1, except that the amount of activated carbon 3 was 0.3748 g, the amount of pullulan (PUL) (0.9%) was 0.0034 g, and the amount of water was 0.3770 g. This was used as Prototype 46, a tablet-type adsorbent for oral administration.

[0103] <Prototype Example 47> A tablet-type adsorbent for oral administration was prepared in the same manner as in Prototype Example 1, except that the amount of activated carbon 4 was 0.5687 g, the amount of pullulan (PUL) (0.6%) was 0.0034 g, and the amount of water was 0.3993 g. This was used as Prototype Example 47, which is a tablet-type adsorbent for oral administration.

[0104] <Prototype Example 48> Except for using 0.5730 g of activated carbon 4, 0.0052 g of pullulan (PUL) (0.9%), and 0.4362 g of water, the same procedure was followed as for the tablet-type adsorbent for oral administration in Prototype Example 1, to give tablet-type adsorbent for oral administration Prototype Example 48.

[0105] <Prototype Example 49> A tablet-type adsorbent for oral administration was prepared in the same manner as in Prototype 1, except that the amount of activated carbon 5 was 0.5219 g, the amount of pullulan (PUL) (0.6%) was 0.0032 g, and the amount of water was 0.3991 g. This was used as Prototype 49, a tablet-type adsorbent for oral administration.

[0106] <Prototype Example 50> A tablet-type adsorbent for oral administration (Prototype Example 50) was prepared in the same manner as the tablet-type adsorbent for oral administration (Prototype Example 1), except that the amount of activated carbon 5 was 0.5224 g, the amount of pullulan (PUL) (0.9%) was 0.0048 g, and the amount of water was 0.4042 g.

[0107] <Prototype Example 51> Except for using 0.3018 g of activated carbon 1, 0.0018 g of hydroxypropyl cellulose (HPC) (0.6%), and 0.2880 g of water, the same procedure was followed as for the tablet-type adsorbent for oral administration in Prototype Example 1, to give tablet-type adsorbent for oral administration in Prototype Example 51.

[0108] <Prototype Example 52> Except for using 0.3008 g of activated carbon 1, 0.0027 g of hydroxypropyl cellulose (HPC) (0.9%), and 0.2811 g of water, the same procedure was followed as for the tablet-type adsorbent for oral administration in Prototype Example 1, to give tablet-type adsorbent for oral administration in Prototype Example 52.

[0109] <Prototype Example 53> Except for using 0.3443 g of activated carbon 2, 0.0021 g of hydroxypropyl cellulose (HPC) (0.6%), and 0.3282 g of water, the same procedure was followed as for the tablet-type adsorbent for oral administration in Prototype Example 1, to give tablet-type adsorbent for oral administration in Prototype Example 53.

[0110] <Prototype Example 54> Except for using 0.3440 g of activated carbon 2, 0.0031 g of hydroxypropyl cellulose (HPC) (0.9%), and 0.3055 g of water, the same procedure was followed as for the tablet-type adsorbent for oral administration in Prototype Example 1, to give tablet-type adsorbent for oral administration in Prototype Example 54.

[0111] <Prototype Example 55> Except for using 0.3744 g of activated carbon 3, 0.0023 g of hydroxypropyl cellulose (HPC) (0.6%), and 0.3561 g of water, the same procedure was followed as for the tablet-type adsorbent for oral administration in Prototype Example 1, to give tablet-type adsorbent for oral administration Prototype Example 55.

[0112] <Prototype Example 56> Except for using 0.3754 g of activated carbon 3, 0.0035 g of hydroxypropyl cellulose (HPC) (0.9%), and 0.2491 g of water, the same procedure was followed as for the tablet-type adsorbent for oral administration in Prototype Example 1, to give tablet-type adsorbent for oral administration in Prototype Example 56.

[0113] <Prototype Example 57> Except for using 0.5687 g of activated carbon 4, 0.0035 g of hydroxypropyl cellulose (HPC) (0.6%), and 0.3141 g of water, the same procedure was followed as for the tablet-type adsorbent for oral administration in Prototype Example 1, to give tablet-type adsorbent for oral administration in Prototype Example 57.

[0114] <Prototype Example 58> Except for using 0.5732 g of activated carbon 4, 0.0052 g of hydroxypropyl cellulose (HPC) (0.9%), and 0.2952 g of water, the same procedure was followed as for the tablet-type adsorbent for oral administration in Prototype Example 1, to give tablet-type adsorbent for oral administration in Prototype Example 58.

[0115] <Prototype Example 59> Except for using 0.5217 g of activated carbon 5, 0.0032 g of hydroxypropyl cellulose (HPC) (0.6%), and 0.4189 g of water, the same procedure was followed as for the tablet-type adsorbent for oral administration in Prototype Example 1, to give tablet-type adsorbent for oral administration in Prototype Example 59.

[0116] <Prototype Example 60> Except for using 0.5248 g of activated carbon 5, 0.0047 g of hydroxypropyl cellulose (HPC) (0.9%), and 0.3689 g of water, the same procedure was followed as for the tablet-type adsorbent for oral administration in Prototype Example 1, to give tablet-type adsorbent for oral administration in Prototype Example 60.

[0117] [Measurement of tablet-type adsorbents for oral administration] [Moldability] In terms of moldability, each prototype was rated as "good" if it could be molded into a tablet, and "bad" if it could not be molded into a tablet or suffered defects such as chipping or cracking during the process of removing it from the mold.

[0118] 〔hardness〕 The hardness (N) was measured using a digital hardness tester (AS ONE Corporation, "KHT-40N"), and the breaking strength at the time when the tablet-type adsorbent for oral administration was broken was taken as the hardness.

[0119] The physical properties of each prototype are shown in Tables 2 to 16. In addition to the tablet formability and hardness (N), the composition includes the type of activated carbon used, the type of additive, the concentration of the additive (%), and the solid-liquid ratio (ml / g). The solid-liquid ratio is the value obtained by dividing the volume of water used in the prototype by the total weight of the activated carbon and additive. The results of prototypes 1 to 20 using sodium carboxymethylcellulose (CMC-Na) as an additive are shown in Tables 2 to 6, the results of prototypes 21 to 40 using hydroxyethylcellulose (HEC) are shown in Tables 7 to 11, the results of prototypes 41 to 50 using pullulan (PUL) are shown in Tables 12 to 14, and the results of prototypes 51 to 60 using hydroxypropylcellulose (HPC) are shown in Tables 14 to 16.

[0120] [Table 2]

[0121] [Table 3]

[0122] [Table 4]

[0123] [Table 5]

[0124] [Table 6]

[0125] [Table 7]

[0126] [Table 8]

[0127] [Table 9]

[0128] [Table 10]

[0129] [Table 11]

[0130] [Table 12]

[0131] [Table 13]

[0132] [Table 14]

[0133] [Table 15]

[0134] [Table 16]

[0135] [Adsorption performance evaluation] The inventors conducted an adsorption test to measure the adsorption rate of nitrogen-containing compounds that may cause uremia, etc. Four types of substances, "indole," "indoleacetic acid," "indoxyl sulfate," and "tryptophan," were selected as toxic substances from nitrogen-containing low molecular weight compounds, and the adsorption rates (%) of the four types of molecules were measured for activated carbons 1 to 5 and each prototype tablet-type adsorbent for oral administration.

[0136] Regarding the adsorption rates of the four substances, each of the substances was dissolved in a phosphate buffer solution of pH 7.4 to prepare a standard solution with a concentration of 0.1 g / l. To 50 ml of the indole standard solution, 0.01 g of each of granular activated carbon 1 to 5, which had been previously dried by heating at 120°C for 15 minutes or more in a static dryer, was added, and the mixture was shaken in contact at 37°C for 3 hours. To 50 ml of the standard solution of indoleacetic acid, 0.01 g of each of granular activated carbons 1 to 5, which had been previously dried by heating at 120°C for 15 minutes or more in a static dryer, was added, and the mixture was shaken in contact at 37°C for 3 hours. To 50 ml of a standard solution of indoxyl sulfate, 0.01 g of each of granular activated carbons 1 to 5, which had been previously dried by heating at 120°C for 15 minutes or more in a static dryer, was added, and the mixture was shaken in contact at 37°C for 3 hours. 0.01 g of each of activated carbons 1 to 5, which had been dried by heating in a static dryer at 120°C for 15 minutes or more, was added to 50 ml of a standard solution of tryptophan, and the mixture was shaken in contact at 37°C for 3 hours.

[0137] Then, the absorbance of the filtrate obtained by filtration was measured by absorptiometry at 279 nm using a spectrophotometer (Shimadzu Corporation, "UVmini-1240"). The adsorption rate (%) of each adsorbed substance was calculated using formula (ii).

[0138]

number

[0139] The adsorption rates of each substance of activated carbon 1 to 5 are shown in Table 17.

[0140] [Table 17]

[0141] The adsorption rate of the tablet-type adsorbent for oral administration was divided by the adsorption rate of each activated carbon used to calculate the degree of decrease in adsorption performance as the adsorption ratio. The results of Experimental Examples 1 to 20 using sodium carboxymethylcellulose (CMC-Na) as an additive are shown in Tables 18 to 22, the results of Experimental Examples 21 to 40 using hydroxyethylcellulose (HEC) are shown in Tables 23 to 27, the results of Experimental Examples 41 to 50 using pullulan (PUL) are shown in Tables 28 to 30, and the results of Experimental Examples 51 to 60 using hydroxypropylcellulose (HPC) are shown in Tables 30 to 32.

[0142] The adsorption rate of each prototype tablet-type adsorbent for oral administration was determined by crushing the tablet-type adsorbent for oral administration appropriately using a spatula, and then heating and drying the tablet-type adsorbent for oral administration at 120°C for 15 minutes or more in a static dryer. Then, 0.01g of the crushed tablet-type adsorbent for oral administration (excluding additives) was added to 50ml of a standard solution of the four substances, and the mixture was shaken in contact at 37°C for 3 hours. Then, the filtrate obtained by filtration was measured for absorbance at 279nm by absorptiometry using a spectrophotometer (Shimadzu Corporation, "UVmini-1240"). The adsorption rate (%) of each adsorbed substance was calculated from the above formula (ii).

[0143] [Table 18]

[0144] [Table 19]

[0145] [Table 20]

[0146] [Table 21]

[0147] [Table 22]

[0148]

Table 23

[0149]

Table 24

[0150]

Table 25

[0151]

Table 26

[0152]

Table 27

[0153]

Table 28

[0154]

Table 29

[0155]

Table 30

[0156]

Table 31

[0157]

Table 32

[0158] [Results / Discussion] As shown in Tables 2 to 16, when the amount of binder added as an additive was 0.6% by weight relative to 100% by weight of the tablet-type adsorbent, it was not possible to form the tablets in the prototypes 41, 43, 45, 51, 53, 55, 57, and 59 using pullulan and hydroxypropyl cellulose. It is considered that the binding force of the binder was not fully exerted due to the low concentration of the additive. In the prototypes 1 to 40 using sodium carboxymethylcellulose or hydroxyethylcellulose as the binder, all of them were able to be well formed into tablets, which showed that sodium carboxymethylcellulose or hydroxyethylcellulose is suitable as a binder with high binding force at a low concentration.

[0159] In addition, although the hardness of the tablet-type adsorbent naturally tends to increase as the concentration of the binder increases, in the case of the prototypes 2, 6, 10, 14, 18, 22, 26, 30, 34, and 38, in which sodium carboxymethylcellulose or hydroxyethylcellulose was used as the binder and the amount added was 0.9% by weight, which is lower than 1.0% by weight, the hardness was higher than 10N, which showed that the tablet-type adsorbent was easy to handle and more suitable. In addition, even in the case of the prototypes 1, 5, 13, 17, 25, 29, and 37, in which the amount of the binder added was 0.6 parts by weight, the hardness was 10N or more, and in the case of the prototypes 9 and 21, the hardness was approximately 10N, and it was understood that sufficient moldability was ensured even with a small amount added.

[0160] In particular, in the prototypes in which sodium carboxymethylcellulose was used as a binder, when added at concentrations of 1.5% by weight and 2.0% by weight, the hardness was higher in the prototypes with an added amount of 1.5% by weight, and it was understood that there was no change even if the amount of binder added was more than a certain amount.

[0161] Next, as shown in the experimental examples 1 to 20 using sodium carboxymethylcellulose as a binder shown in Tables 18 to 22, when the experimental examples 1 to 12 using activated carbon 1 to 3, which is an activated carbon with a low packing density, are compared with the experimental examples 13 to 20 using activated carbon 4 and 5, which is an activated carbon with a high packing density, the adsorption rate and adsorption ratio of indole acetic acid and indoxyl sulfate in the experimental examples 13 to 20 using activated carbon 4 and 5 were significantly inferior. Since activated carbon with a high packing density has a large amount of carbon and few pores, even a small amount of additives has a large effect on the adsorption rate, and it is considered that the adsorption performance of the activated carbon raw material is greatly reduced when it is molded into a tablet shape. For this reason, it is preferable that the activated carbon used in the tablet-type adsorbent has a low packing density, especially a packing density of 0.3 to 0.5 g / ml.

[0162] Furthermore, it was found that the balance of the pores formed in the activated carbon also contributes to the adsorption performance of toxic substances and to the prevention of the decrease in the adsorption performance when it is formed into a tablet. m ) indicates that the micropores and mesopores are well-balanced in their development, and the presence of sufficient macropores and a certain amount of mesopores allows the toxic substances to be adsorbed to smoothly pass from the macropores through the mesopores to the micropores and be adsorbed. Furthermore, since it is believed that a certain amount of pores are blocked by the binder, it is believed that using activated carbon with more developed mesopores than ordinary activated carbon can prevent a decrease in adsorption performance when formed into a tablet. For this reason, the volume ratio (V m It is advisable to use activated carbon with a pH of 5.0 or less.

[0163] In addition, as shown in Tables 23 to 27, in addition to the packing density and volume ratio, the specific surface area is 1400 m 2 / g or more, it was found that the decrease in the adsorption performance for indole acetic acid can be further suppressed.

[0164] The types of binders are shown in Tables 18 to 32. As mentioned above, pullulan and hydroxypropyl cellulose are not very suitable for tableting with a small amount of addition, and when comparing the prototypes using sodium carboxymethylcellulose or hydroxyethyl cellulose with those using pullulan or hydroxypropyl cellulose, the adsorption performance of the activated carbon raw material is greatly reduced when the activated carbon is formed into a tablet. Therefore, it is possible to form activated carbon into a tablet shape even with a small amount of addition, and it was shown that sodium carboxymethylcellulose or hydroxyethyl cellulose is suitable as an additive as a binder that can suppress the decrease in the adsorption performance of activated carbon.

[0165] As shown in Tables 18-20, 23-25, when the amount of additive as a binder is 1% by weight or less, it was shown that the decrease in adsorption performance when the raw activated carbon is molded into a tablet shape can be suppressed. It is easy to understand that the decrease in adsorption performance caused by the pores of the activated carbon being blocked by the binder can be suppressed by reducing the amount of binder added. However, in view of the physical properties of the activated carbon shown in Tables 1-32 and the measurement results of the tablet-type adsorbents of each prototype, it was found that not only the amount of binder added but also the physical properties of the raw activated carbon and the type of binder contribute to suppressing the decrease in adsorption performance.

[0166] [summary] As shown in each prototype, it was found that a tablet-type adsorbent formed into a tablet shape by adding a very small amount of sodium carboxymethylcellulose or hydroxyethylcellulose as an additive to activated carbon with a low packing density as the base carbon can suppress the decrease in the adsorption performance of toxic substances of the base carbon. It was also found that by reducing the volume ratio of the sum of the mesopore volumes to the sum of the micropore volumes, even if the additive is adsorbed in the macropores or mesopores, the toxic substances are less likely to be hindered from reaching the micropores, which contributes to suppressing the decrease in the adsorption performance of the tablet-type adsorbent for oral administration. It was shown that by using sodium carboxymethylcellulose or hydroxyethylcellulose as an additive, it has a certain hardness even in a very small amount, and is suitable for a tablet-type adsorbent. [Industrial Applicability]

[0167] The tablet-type adsorbent for oral administration of the present invention can suppress the decrease in the adsorption performance of activated carbon, which is an adsorbent with high adsorption performance for toxic substances, and therefore can be easily taken and suppresses an increase in the dosage and volume, thereby reducing the burden on patients. In addition, since it is easy to take, it can reach the digestive organs by oral administration and rapidly adsorb nitrogen-containing compounds that cause uremia, renal dysfunction, liver dysfunction, etc., and is therefore promising as a therapeutic or preventive agent.

Claims

1. A tablet-type adsorbent for oral administration, comprising granular or spherical activated carbon as an adsorbent and an additive as a binder, The additive contains at least one of sodium carboxymethylcellulose and hydroxyethylcellulose, and is added in an amount of 1.0% by weight or less based on 100% by weight of the tablet-type adsorbent.

1. A tablet-type adsorbent for oral administration.

2. 2. The tablet-type adsorbent for oral administration according to claim 1, wherein the average particle size of the activated carbon is 20 to 1000 μm.

3. 3. The tablet-type adsorbent for oral administration according to claim 1, wherein the tablet-type adsorbent has a hardness of 10 N or more.

4. The micropore volume (V mic ) to mesopore volume (V met ) volume ratio (V m 4. The tablet-type adsorbent for oral administration according to claim 1, wherein the molecular weight distribution (Mg / mol) is 5.0 or less. [0010]

5. 5. The tablet-type adsorbent for oral administration according to claim 1, wherein the activated carbon is a resin carbonized product of a phenol resin.

Citation Information

Patent Citations

  • Chemical compound and production and utilization thereof

    JP1982001971A

  • Water purifier

    JP1993169056A

  • Anti-nephrosis syndrome agent

    JP1994135841A

  • Activated carbon, its manufacturing method, and renal disease therapeutic drug

    JP2006131461A

  • Adsorbing agent for medical use

    JP2008303193A